Faith versus fact : why science and religion are incompatible - Coyne, Jerry A., 1949- (New York : Viking, 2015)
The best-selling author of Why Evolution Is True discusses the negative role of religion in education, politics, medicine and social policy, explaining how religion cannot provide verifiable or responsible answers to world problems.
The problem -- What's incompatible?. What is science? ; What is religion? ; The incompatibility ; Conflicts of method ; Conflicts of outcome ; Conflicts of philosophy -- Why accommodationism fails. The varieties of accommodationism ; Science versus the supernatural ; What about miracles? ; Three test cases ; Was the evolution of humans inevitable? ; Theological problems with theistic evolution -- Faith strikes back. The new natural theology ; Is science the only "way of knowing"? ; The scientism canard -- Why does it matter?. Child abuse : faith as substitute for medicine ; Suppression of research and vaccination ; Opposition to assisted dying ; Global-warming denialism ; Does faith have any value? ; Can there be dialogue between science and faith?
Includes bibliographical references (pages 281-296) and index.
Keywords: Religion and science; Faith and reason